AS MULHERES COMO PILAR DA CONSTRUÇÃO DOS PROGRAMAS SOCIAIS - Garcia dos Santos, Yumi (Caderno CRH, 2015)
<p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Este artigo analisa o modo como as políticas públicas voltadas para a saúde e a assistência social no Brasil se consolidam a partir da centralidade da atuação das mulheres pobres. Por meio de uma pesquisa qualitativa e de análise das trajetórias das usuárias e das agentes de ponta dos ditos "novos" programas sociais brasileiros, pretende-se mostrar que o sucesso que tais programas têm conquistado depende, em grande medida, da atuação dessas mulheres mediadoras dentro da lógica conservadora da divisão sexual do trabalho e da disposição feminina para o cuidado. Em particular, as agentes, em contraponto às usuárias, têm acesso à mobilidade social que as tira do confinamento na esfera privada pela sua presença no mercado de trabalho. No entanto, o maior ganho dessa mobilização feminina a baixo custo e de alta produtividade é direcionado às instituições gestoras dos "novos" programas sociais em questão, desde as organizações filantrópicas até os governos. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Palavras-chave : "Novos" programas sociais; Mediação feminina; Família; Trabalho; Divisão sexual do trabalho. <strong style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"> Women as the strength behing social programs <span style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Yumi Garcia dos Santos<strong style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"> <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">This article examines how public policies for health and social care in Brazil are consolidated with the actions of poor women. Through a qualitative research and analysis of the trajectories of these users and top agents of the so called "new" Brazilian social programs, I intend to show that the success such programs have achieved is largely due to the work of these women, who are mediators within the conservative logic of a gender bias division of labor and denomination of women as caregivers. In particular, the agents, as opposed to the users, have access to social mobility that frees them from the confinement of their private sphere by being present in the labor market. However, this female mobilization, with low costs and high productivity, benefits mainly the institutions of the "new" social programs in question, from philanthropic organizations to governmental ones. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Keywords:"New" social programs; Feminine mediation; Family; Work; Gender bias labor division. <span class="article-title" style="font-weight: bold; color: #000000; font-family: verdana,arial; font-size: 13.192px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Les femmes comme piliers de la construction des programmes sociaux.<em style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"> <span style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Yumi Garcia dos Santos<em style="color: #000000; font-family: verdana,arial; font-size: 13.192px; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"> <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Cet article analyse comment les politiques publiques en matière de santé et d’aide sociale au Brésil se consolident à partir de la centralité d’action des femmes pauvres. Grâce à une recherche qualitative et à une analyse de la trajectoire des utilisatrices et des agents des dits "nouveaux" programmes sociaux brésiliens, notre intention est de montrer que le succès de ces programmes dépend en grande partie de l’action de ces femmes médiatrices au sein d’une logique conservatrice de la division sexuelle du travail et d’un enclin féminin pour les soins. Les agents, en opposition aux usagers, ont tout particulièrement accès à la mobilité sociale qui les sort du confinement de la sphère privée par leur présence sur le marché du travail. Cependant le résultat le plus important, obtenu grâce à cette mobilisation féminine à faible coût mais dont la productivité est élevée, bénéficie les institutions qui gèrent ces "nouveaux" programmes sociaux en question, allant des organisations philanthropiques aux gouvernements. <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Mots-clés: "Nouveaux" programmes sociaux; Médiation féminine; Famille; Travail; Division sexuelle du travail. <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <br style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;" /> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; display: inline ! important; float: none; background-color: #ffffff;"> <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;"> <p style="font-size: 13.192px; color: #000000; font-family: verdana,arial; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; background-color: #ffffff;">